2023
DOI: 10.1093/bib/bbad172
|View full text |Cite
|
Sign up to set email alerts
|

Phen2Disease: a phenotype-driven model for disease and gene prioritization by bidirectional maximum matching semantic similarities

Abstract: Human Phenotype Ontology (HPO)-based approaches have gained popularity in recent times as a tool for genomic diagnostics of rare diseases. However, these approaches do not make full use of the available information on disease and patient phenotypes. We present a new method called Phen2Disease, which utilizes the bidirectional maximum matching semantic similarity between two phenotype sets of patients and diseases to prioritize diseases and genes. Our comprehensive experiments have been conducted on six real da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The most important feature for both VP and predicting the genomic test results was the symptom similarity between the patient’ phenotypes and the disease phenotypes. This finding is in line with previous research that also suggested phenotype-driven approach to be effective in variant filtering and identification of the disease-causing variants 34 . To the best of our knowledge, the dataset that we used to evaluate our model is the largest real-world rare disease patient’s sequencing data that has been used for evaluation VP tools.…”
Section: Discussionsupporting
confidence: 92%
“…The most important feature for both VP and predicting the genomic test results was the symptom similarity between the patient’ phenotypes and the disease phenotypes. This finding is in line with previous research that also suggested phenotype-driven approach to be effective in variant filtering and identification of the disease-causing variants 34 . To the best of our knowledge, the dataset that we used to evaluate our model is the largest real-world rare disease patient’s sequencing data that has been used for evaluation VP tools.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to analyzing the properties of the variants, utilizing clinical phenotypes to help the diagnosis is crucial. As patients’ clinical phenotypes can be documented by the Human Phenotype Ontology (HPO) terminology [ 3 ], many computational approaches have been developed based on HPO terms to diagnose rare diseases [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. In addition, many rare diseases often present a characteristic pattern of facial features called “facial gestalt”.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Lu et al ( 12 ) investigated the MicroRNA-17’s functions as an oncogene by inhibiting Smad3 expression in carcinoma of the liver. A phenotype-driven paradigm for disease and gene prioritization via bidirectional optimum corresponding lexical commonalities was discovered by Zhai et al ( 13 ). A disease–gene association prediction algorithm that is interpretable from commencement to completion was proposed by Li et al ( 14 ).…”
Section: Introductionmentioning
confidence: 99%